Islamic Extremism Strategy of “Near and Far Enemy” (From the 1980s Till Now) - Grigoryan, Sargis (Տիգրան Մեծ)
In the 1980s, the “Al-Qaeda” launched the tactics of the struggle against the “Near and Far Enemy”. It found its ideological grounds in the Islamic extremism in the 1980-90s with practical implications, affecting the current geopolitical and global economic trends in the Muslim world and well beyond it. In the Islamic extremism ideology, this strategy also received textual-substantive justifications of symbolic perceptions, which, of course, influenced the behaviour of extremists. The present research attempts to investigate the peculiarities of the tactics mentioned, which were masterminded and enriched by the ideologists of Islamic extremism, becoming one of the motives of the activities of Islamic extremists starting from the 1980s up to the current developments and one of the grounds for targets of Jihad.
Keywords: Social philosophy